Molecular Characterization of Ampicillin-Resistant Enterococcus faecium Isolates from Hospitalized Patients in Norway - Jureen, Roland (American Society for Microbiology, 2003)
The genetic relationship of 81 ampicillin-resistant and 21 ampicillin-susceptible Enterococcus faecium isolates from clinical infections and rectal screening in hospitalized patients in Norway was studied by pulsed-field gel electrophoresis (PFGE) and amplified fragment length polymorphism (AFLP). PFGE showed 55 different banding patterns, and 65 of the isolates could be grouped into one large group. With AFLP, 46 patterns were discerned, and 74 isolates clustered in one group. In general, the isolates had a higher degree of similarity than with PFGE. The purK gene, which is one of the targets of the E. faecium multilocus sequence typing scheme, was sequenced. Eleven different purK alleles could be discerned, with the majority of isolates (n = 80) harboring allele 1. With only two exceptions, all strains carrying purK-1 clustered in the same PFGE and AFLP groups, indicating a good correlation between PFGE type, AFLP type, and purK allele. Genetic polymorphism of a 571-bp PCR fragment of the C-terminal domain of the penicillin-binding protein 5 gene (pbp5) was determined, and sequence differences were associated with the level of ampicillin resistance. This study indicates that the majority of ampicillin-resistant E. faecium strains in Norway belong to a distinct genetic lineage of closely related genotypes. Rectal and clinical isolates were generally indistinguishable, and differences in clonal distribution and allele polymorphism were found mainly between ampicillin-resistant and -susceptible isolates.